Somalis Abroad : Clan and Everyday Life in Finland - Bjork, Stephanie R. (Book collections on Project MUSE., 2017)
Drawing on a wealth of ethnographic detail, Stephanie Bjork offer the first study on the messy role of clan or tribe in the Somali diaspora, and the only study on the subject to include women's perspectives. 'Somalis Abroad' illuminates the ways clan is contested alongside ideas of autonomy and gender equality, challenged by affinities towards others with similar migration experiences, transformed because of geographical separation from family members, and leveraged by individuals for cultural capital. Challenging prevailing views in the field, Bjork argues that clan-informed practices influence everything from asylum decisions to managing money. The practices also become a pattern that structures important relationships via constant - and unwitting - effort.